2009
DOI: 10.1149/1.3076137
|View full text |Cite
|
Sign up to set email alerts
|

Capacity-Fading Mechanisms of LiNiO[sub 2]-Based Lithium-Ion Batteries

Abstract: We used a suite of transmission electron microscopy (TEM) and associated electron spectroscopy methods to examine the local structure and changes in the electronic structure of LinormalNi0.8normalCo0.15normalAl0.05normalO2 positive electrode material. We found a scattered rock-salt phase near grain surfaces and grain boundaries, where Ni3+ turned to Ni2+ , deduced from relative intensity ratios and fine structures of the L2,3 white-line peaks of the transition metals. The spatial distribution of the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
151
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(162 citation statements)
references
References 26 publications
11
151
0
Order By: Relevance
“…We also successfully applied NMF to a series of EELS datasets for the extraction of atom site-specific core-loss spectra, where the relative excitation probabilities of the spectra varied with the diffraction condition because of the electron channeling effects [22][23][24][25]. In these applied data analyses, the nonnegative constraint of the elements of extracted basis spectra and spatial intensity distributions were effective, and the resulting spectra extracted by NMF were consistent with the computational results obtained by first principles calculations [15][16][17][18][19][22][23][24][25].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…We also successfully applied NMF to a series of EELS datasets for the extraction of atom site-specific core-loss spectra, where the relative excitation probabilities of the spectra varied with the diffraction condition because of the electron channeling effects [22][23][24][25]. In these applied data analyses, the nonnegative constraint of the elements of extracted basis spectra and spatial intensity distributions were effective, and the resulting spectra extracted by NMF were consistent with the computational results obtained by first principles calculations [15][16][17][18][19][22][23][24][25].…”
Section: Introductionsupporting
confidence: 65%
“…Contrary to NMF, the methods mentioned above such as PCA allow the spatial intensities and spectra to have negative values, which hampers the direct physical interpretation of the resolved spectral profiles. We adopted the modified alternating least-square (MALS) fitting algorism of NMF [14] to map the different phases in the degradation of Li battery cathodes [15][16][17][18][19] and the chemical states of nitrogen in nitrogen-doped TiO 2 [20,21]. We also successfully applied NMF to a series of EELS datasets for the extraction of atom site-specific core-loss spectra, where the relative excitation probabilities of the spectra varied with the diffraction condition because of the electron channeling effects [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…31 Even though it was not explicitly shown in these latter reports, the observed phase transitions suggest a release of oxygen from the particle surface, which was also pointed out in the reports by Abraham et al, Muto et al, and Hwang et al [28][29][30][31] So far, a release of oxygen from the oxide lattice under battery operating conditions was shown only for overlithiated NMC materials (Li 1+x (Ni,Mn,Co) 1-x O 2 ), in which lithium additionally occupies the transition metal layers. [32][33][34][35][36] The exception is a recent publication by Guéguen et al, who showed oxygen evolution during battery cycling for NMC111.…”
mentioning
confidence: 63%
“…The ALS method was applied to these EELS data [7][8][9][10][11][13][14][15]. As an initial ALS estimation, the orthogonal projection approach (OPA) was used [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…Such a large matrix of spectral data is suitable for analysis via a chemometrics approach. To obtain individual pure spectra from the series of spectra without a reference spectrum, we applied a self-modeling curve-resolution technique (the alternating least-squares (ALS) method) [7][8][9][10][11] to the series of spectra to perform spectral decomposition. The degradation process of LiCoO 2 was analyzed based on the series of decomposed spectra.…”
Section: Introductionmentioning
confidence: 99%